Current status of adherence interventions in hypertension management in Asian countries: A report from the HOPE Asia Network. Issue 3 (17th December 2020) - Shin, Jinho; Chia, Yook‐Chin; Heo, Ran; Kario, Kazuomi; Turana, Yuda; Chen, Chen‐Huan; Hoshide, Satoshi; Fujiwara, Takeshi; Nagai, Michiaki; Siddique, Saulat; Sison, Jorge; Tay, Jam Chin; et al.
Abstract: Adherence continues to be the major hurdle in hypertension management. Since the early 2000s, systematic approaches have been emphasized to tackle multi‐dimensional issues specific for each regional setting. However, there is little data regarding implementation of adherence interventions in Asian countries. Eleven hypertension experts from eight Asian countries answered questionnaires regarding the use of adherence interventions according to 11 theoretical domain frameworks by Allemann et al. A four‐point Likert scale: Often, Sometimes, Seldom, and Never used was administered. Responses to 97 items from 11 domains excluding three irrelevant items were collected. "Often‐used" interventions accounted for 5/9 for education, 1/8 for skills, 1/2 for social/professional role and identity, 1/1 for belief about capabilities, 0/3 for belief about consequences, 2/4 for intentions, 2/9 for memory, attention, and decision process, 11/20 for environmental context and resources, 0/2 for social influences, 0/2 for emotion, and 2/2 for behavioral regulation. Most of them are dependent on conventional resources. Most of "Never used" intervention were the adherence interventions related to multidisciplinary subspecialties or formal training for behavioral therapy. For adherence interventions recommended by 2018 ESC/ESH hypertension guidelines, only 1 in 7 patient level interventions was "Often used." In conclusion, conventional or physician level interventions such as education, counseling, and prescription have been well implemented but multidisciplinary interventions and patient or health system level interventions are in need of better implementation in Asian countries.